Analisis Pengaruh Pemakaian Material Kerikil Gunung Kecamatan Mantup dan Serat Alami Eceng Gondok Terhadap Kuat Tekan Dan Kuat Lentur Beton - Rio Rahma Dhana (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2019)
Basically, concrete has some basic characteristics, thoseare strong to the compressive stress and weak to the tensile stress. The compressive strength of the concrete is influenced by the type of constituent material. If the constituent material is good, solid, then it will produce a concrete that has a high compressive strength. In this case it is planned by adding mountain gravel from Mantup District and natural fiber from water hyacinth at 0%, 4%, 6%, and 8% on concrete compressive strength. This research usesexperimentalmethod, where the gravel from Mantup replaces the common gravel and addition of water hyacinth fiber calculated from the proportion of cement weight used. By using cylindrical test object, it is made 3 test objects for each percentage sample of water hyacinth fiber, so that the result of concrete compressive strength obtained later can be compared to the results. Based on the concrete compressive strength test, the scores of compressive strength in the age of 7 days which then correlated to the age of  28 days ie 0% (9,30Mpa), 4% (6,61 Mpa), 6% (5,66 Mpa), and 8% (3,77 Mpa).